Combining battery-like and pseudocapacitive charge storage in 3D MnOx@carbon electrode architectures for zinc-ion cells. Issue 3 (4th January 2018) - Ko, Jesse S.; Sassin, Megan B.; Parker, Joseph F.; Rolison, Debra R.; Long, Jeffrey W.
Abstract : Nanoscale MnO x expressed in 3D carbon nanofoam electrodes exhibits both pseudocapacitive and battery-like charge-storage using a mixed Na +  : Zn 2+ aqueous electrolyte. Abstract : We demonstrate that electrodes comprising nanoscale, birnessite-type manganese oxide affixed to carbon nanofoam paper (MnO x @CNF) exhibit two distinct charge-storage mechanisms—battery-like Zn 2+ insertion/de-insertion and pseudocapacitance—when electrochemically cycled in aqueous electrolytes that include both Na + and Zn 2+ salts. When the mixed-electrolyte composition is 0.75 M Na2 SO4 + 0.25 M ZnSO4 ( i.e., "6[Na + ] : 1[Zn 2+ ]"), the MnO x @CNF electrode delivers high specific capacity at low rates, approaching theoretical capacity for Zn 2+ insertion/de-insertion at MnO x . At high rates (>10C) the Na + -supported pseudocapacitance mechanism maintains charge-storage capacity well above that observed with electrolytes that contain only ZnSO4 . Impedance analysis was performed to discriminate between these distinct charge-storage mechanisms by visualizing the frequency- and potential-dependent capacitance as 3D Bode plots. In the 6[Na + ] : 1[Zn 2+ ] electrolyte, the potential-independent pseudocapacitance is augmented by reversible Zn 2+ -based redox processes between 1.4 and 1.8 V vs. Zn/Zn 2+ . Galvanostatic testing with two-electrode zinc-ion cells that pair MnO x @CNF with a zinc foil negative electrode proves the practical performance advantages of combining pseudocapacitance and Zn 2+ -insertion mechanisms: higher energy efficiency and greater specific power in the 6[Na + ] : 1[Zn 2+ ] electrolyte compared to 1 M ZnSO4 .